The Oncolytic Virus dl922-947 Triggers Immunogenic Cell Death in Mesothelioma and Reduces Xenograft Growth - Di Somma, Sarah; Iannuzzi, Carmelina Antonella; Passaro, Carmela; Forte, Iris Maria; Iannone, Raffaella; Gigantino, Vincenzo; Indovina, Paola; Botti, Gerardo; Giordano, Antonio; Formisano, Pietro; Portella, Giuseppe; Malfitano, Anna Maria; et al. (Frontiers in Oncology, 2019)
Background: Malignant pleural mesothelioma (MPM) is an aggressive cancer associated with asbestos exposure that urgently requires effective therapeutic strategies. Current treatments are unable to increase significantly patient survival, which is often limited to <1 year from diagnosis. Virotherapy, based on the use of oncolytic viruses that exert anti-cancer effects by direct cell lysis and through the induction of anti-tumor immune response, represents an alternative therapeutic option for rare tumors with limited life expectancy. In this study, we propose the use of the adenovirus dl922-947, engineered to allow selective replication in cancer cells, to counteract MPM. Methods: We performed a thorough preclinical assessment of dl922-947 effects in a set of MPM cell lines and xenografts. Cytotoxicity of dl922-947 alone and in combination assays was evaluated by sulforhodamine B assay. Cell cycle, calreticulin expression, and high mobility group box protein 1 (HMGB1) secretion were determined by flow cytometry, whereas ATP content was determined by a luminescence-based bioassay. The modulation of angiogenic factors in MPM-infected cells was evaluated through ELISA. Results: We found that dl922-947 infection exhibits cytotoxic effects in MPM cell lines, affecting cell viability, cell cycle progression, and regulating main hallmarks of immunogenic cell death inducing calreticulin surface exposure, HMGB1 and ATP release. Our results also suggest that dl922-947 may affect angiogenic signals by regulation of VEGF-A and IL-8 secretion. Furthermore, dl922-947 shows anti-tumor efficacy in murine xenograft models reducing tumor growth and enhancing survival. Finally, the combination with cisplatin potentiated the cytotoxic effect of dl922-947. Conclusions: Overall our data identify virotherapy, based on the use of dl922-947, as a new possible therapeutic strategy against MPM, which could be used alone, in combination with standard chemotherapy drugs, as shown here, or other approaches also aimed at enhancing the antitumoral immune response elicited by the virus.